PENGOLAHAN LIMBAH PLASTIK MENJADI PRODUK KREATIF SEBAGAI PENINGKATAN EKONOMI MASYARAKAT PESISIR - Zulfan Arico; Sri Jayanthi (Martabe : Jurnal Pengabdian Kepada Masyarakat, 2017)
ncreasing garbage in Langsa City especially in Gampong Kuala Langsa will become a serious problem if not solved. On the one hand, the invention of this plastic has a tremendous positive effect, because plastic has advantages over other materials. Based on these analyzes, the community service activities need to be done with the aim of improving the economy of Langsa City, especially coastal communities. Based on the results of further evaluation also recorded, some of the practical benefits gained by mothers in the village of Kuala Langsa, that is they get clear and whole information about the essence of community empowerment in terms of knowledge and skills. Meaningful for created of new jobs that are innovative from development of home industry, mothers who participated in the training obtained a clear picture of the business climate development step by using waste of coffee wrap, trainees also get a clear and whole picture about the benefits of waste if managed properly. The next stage plan is Assistance to the processing of plastic waste into a product so as to obtain quality standard both quality and quantity of quality and product quality and evaluation program to see how far the program is beneficial for mothers in the village of Kuala Langsa.Keywords: Creative Product, Kuala Langsa, Plastic Waste.